Drug-Induced Long QT Syndrome - Kannankeril, Prince (The American Society for Pharmacology and Experimental Therapeutics, 2010)
The drug-induced long QT syndrome is a distinct clinical entity that has evolved from an electrophysiologic curiosity to a centerpiece in drug regulation and development. This evolution reflects an increasing recognition that a rare adverse drug effect can profoundly upset the balance between benefit and risk that goes into the prescription of a drug by an individual practitioner as well as the approval of a new drug entity by a regulatory agency. This review will outline how defining the central mechanism, block of the cardiac delayed-rectifier potassium current I(Kr), has contributed to defining risk in patients and in populations. Models for studying risk, and understanding the way in which clinical risk factors modulate cardiac repolarization at the molecular level are discussed. Finally, the role of genetic variants in modulating risk is described.